Analisis Pemajasan Pada Lirik Lagu Band Nidji dan Penerapannya pada Pembelajaran Mengidentifikasi Unsur-unsur Puisi di SMA Kelas X - Nuryuliasih Nuryuliasih (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study is to describe: (1) the figurative meanings contained in the lyrics of Nidji's song; (2) the imagery contained in the lyrics of the song Nidji; and (3) the application of Nidji's song lyrics in learning to identify the elements of poetry in class X SMA. The data collection of this research was carried out using the observation method. The data analysis of this research is content analysis. The results of data analysis are presented with informal techniques. Based on the data and discussion, it is concluded that (1) the figurative meanings contained in the lyrics of the Nidji song include (a) hyperbole figure of speech which serves to exaggerate the situation when someone is in love. His heart blossomed and everything became beautiful; (b) association figure of speech serves to describe different vibrations when falling in love with millions of feelings; (2) The types of imagery in Nidji's song lyrics consist of (a) auditory images found in the lyrics